Implementation of flipped learning to increase student learning activeness in the combustion engine lecture - Ranto Ranto; Antika Wulandari; Ngatou Rohman (Jurnal Pendidikan Vokasi, 2024)
This study aims to determine the increase in learning activeness of Sebelas Maret University students in the mechanical engineering education study program through the implementation of a flipped learning model in the combustion engine lecture. This research is classroom action research. The action taken is to apply the flipped learning model in the combustion engine lecture. The subjects of this study were 42 students in the second semester of the mechanical engineering education study program. This classroom action research design refers to the Kemmis and Taggart model. The research was conducted in three cycles, each consisting of planning, implementation, observation, and reflection. Data collection was done through observation, interviews, and documentation. The instrument validity test was carried out with construct validity using expert opinions. Data analysis was carried out in a comparative-descriptive way. The results of this classroom action research show that implementing the flipped learning model can increase the learning activeness of students in the combustion engine lecture. In the pre-cycle stage, student learning activeness only reached 45.24% of active learning students. In cycle 1, by implementing a flipped learning model, students learning activeness reached 81.99%, cycle 2 increased to 87.43%, and cycle 3 increased to 91.74%.  The conclusion of this research is that the implementation of the flipped learning model can increase the learning activeness of the mechanical engineering education study program Sebelas Maret University students in the combustion engine lecture. Based on the results of this research, it is highly recommended to use the flipped learning model in lectures, especially in vocational education, increasing student learning activeness will have an impact on increasing student learning achievement.